Global Stable Isotope Dataset for Surface Water - R. Li; R. Li; R. Li; G. Zhu; G. Zhu; G. Zhu; L. Chen; L. Chen; L. Chen; X. Qi; S. Lu; S. Lu; et al. (Earth System Science Data)
Hydrogen and oxygen stable isotopes are widely used as tracers of the water cycle, and surface water is an integral part of the water cycle. Compared with other waterbodies, surface water is more susceptible to different natural and anthropogenic factors, and an accurate understanding of surface water changes is of great significance in ensuring regional water security, maintaining ecological balance, and promoting sustainable economic and social development. The spatial and temporal distributions of global surface water stable isotope data are extremely uneven on a global scale due to factors such as observation conditions and instrumental analysis. For this reason, we have compiled and analysed the stable hydrogen and oxygen isotope data in surface water from 22 389 sampling stations worldwide from 1956 to 2023, with 102 511 data records. The results indicate the following: (1) global surface water stable isotopes are gradually depleted from the Equator to the poles and from the coast to the interior. However, there are significant differences in the spatial and temporal distributions of surface water isotopes in different regions. (2) The variation in stable isotopes in surface water is controlled by geographic location, topographic conditions and meteorological factors (especially temperature), and its heterogeneity is considerable. The global stable isotope dataset of surface water provides vital information for an in-depth understanding of the water cycle and climate change. It can provide essential data references for global water resource management and research. The Global Stable Isotope Dataset for Surface Water is available at https://doi.org/10.17632/fs7rwp7fpr.2 (Zhu, 2024).